2000
DOI: 10.1099/00207713-50-2-547
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of Thiobacillus denitrificans as a species of the genus Thiobacillus, in the beta-subclass of the Proteobacteria, with strain NCIMB 9548 as the type strain.

Abstract: NOTE Confirmation of Thiobacillus denitrificans as a species of the genus

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
85
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(86 citation statements)
references
References 29 publications
0
85
0
1
Order By: Relevance
“…Following the reclassification of numerous ␣-, ␤-, and ␥-proteobacterial species previously classified as Thiobacillus spp., only three ␤-proteobacteria are now securely placed in that genus: T. thioparus, T. denitrificans, and T. aquaesulis (47,49). Of these, the last is a moderate thermophile and only T. denitrificans is capable of strictly chemolithotrophic anaerobic growth with denitrification using inorganic sulfur-compound oxidation as the sole source of energy (46,49).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the reclassification of numerous ␣-, ␤-, and ␥-proteobacterial species previously classified as Thiobacillus spp., only three ␤-proteobacteria are now securely placed in that genus: T. thioparus, T. denitrificans, and T. aquaesulis (47,49). Of these, the last is a moderate thermophile and only T. denitrificans is capable of strictly chemolithotrophic anaerobic growth with denitrification using inorganic sulfur-compound oxidation as the sole source of energy (46,49).…”
Section: Resultsmentioning
confidence: 99%
“…Thiobacillus denitrificans, first isolated by Beijerinck over a century ago (4), was one of the first nonfilamentous bacteria ever described to be capable of growth on inorganic sulfur compounds as sole energy sources (47,49). Characterized by its ability to conserve energy from the oxidation of inorganic sulfur compounds under either aerobic or denitrifying conditions, T. denitrificans is the best studied of the very few obligate chemolithoautotrophic species known to couple denitrification to sulfur-compound oxidation (Thiomicrospira denitrificans and Thioalkalivibrio thiocyanodenitrificans also have this ability [76,85]).…”
mentioning
confidence: 99%
“…In this article, it is reported that the widely distributed, obligate chemolithoautotrophic bacterium Thiobacillus denitrificans, known for its ability to couple the oxidation of various S-and Fe(II)-containing electron donors with denitrification (8,15), is capable of anaerobic, nitrate-dependent oxidative dissolution of synthetic and biogenic U(IV) oxides. T. denitrificans has relevance to certain uranium-contaminated sites, as this species (or species with Ͼ98% 16S rRNA gene sequence similarity) was found to account for a relatively large proportion of the bacterial community from an open-pit uranium mine (representing ϳ24% of the 16S rRNA gene clones analyzed [16]).…”
mentioning
confidence: 99%
“…Thiobacillus denitrificans is mainly characterized by its ability to grow as a facultative anaerobic and chemolithoautotroph microorganism [56]. This organism can carry out denitrification and sulfur oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…In denitrification, Thiobacillus may use sulfur compounds and nitrate, nitrite or nitrous oxide as terminal respiratory oxidants, but the sulfur oxidizing enzymes involved in aerobic or anaerobic conditions are still unknown. Moreover, the optimal temperature for the growth of Thiobacillus is 28 to 32 °C with a pH of 6 to 7.4 [56,57], i.e. the temperature range found in the anaerobic digester studied.…”
Section: Discussionmentioning
confidence: 99%